Determinan Intra-Industry Trade Komoditi Kosmetik Indonesia dengan Mitra Dagang Negara ASEAN-5 - Kurniawan, I Putu; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
ASEAN is form of geo-political and economic integration countries in Southeast Asia. Intra industry trade patterns occur in cosmetic commodities Indonesia. The purpose of this research to know degree of integration between five trading partner with Indonesia and factor that becomes determinant of intra industry trade.This research was conducted in the ASEAN with a focus Indonesia's trade partners. The object of the research is the index intra industry Indonesia and the determinant factors affected it approaches based on gravity model. The technique analysis is IIT Index and GLS. Based on the results showed the degree of integration is in middle category. All determinant factor simultaneously has an impact on the degree of integration. Partially just the exchange rate has no effect. Advice from research Government designed the policy of international trade. Keywords : Economic Integration, Intra Industry Trade, IIT Index